1999
DOI: 10.1074/jbc.274.40.28674
|View full text |Cite
|
Sign up to set email alerts
|

Rat B2 Sequences Are Induced in the Hippocampal CA1 Region After Transient Global Cerebral Ischemia

Abstract: Global brain ischemia causes cell death in the CA1region of the hippocampus 3-5 days after reperfusion. The biological pathway leading to such delayed neuronal damage has not been established. By using differential display analysis, we examined expression levels of poly(A) RNAs isolated from hippocampal extracts prepared from rats exposed to global ischemia and found an up-regulated transcript, clone 17a. Northern blot analysis of clone 17a showed an approximately 35-fold increase in the ischemic brain at 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…On the basis of these criteria, we have succeeded in isolating two genes through DD analysis. One is identical to the B2 sequences recently reported as an up-regulated gene (Liu et al, 1999). Unfortunately, the B2 sequences protein has not been detected yet; however, it is speculated to be involved in gene expression and RNA processing (Krayev et al, 1982).…”
Section: Isolation and Identification Of Pi 4-ksupporting
confidence: 56%
See 2 more Smart Citations
“…On the basis of these criteria, we have succeeded in isolating two genes through DD analysis. One is identical to the B2 sequences recently reported as an up-regulated gene (Liu et al, 1999). Unfortunately, the B2 sequences protein has not been detected yet; however, it is speculated to be involved in gene expression and RNA processing (Krayev et al, 1982).…”
Section: Isolation and Identification Of Pi 4-ksupporting
confidence: 56%
“…1C). However, we have identified that the rat B2 sequence, which has been already reported, was transiently up-regulated, peaking at 1 day after brain ischemia in hippocampus but not cerebral cortex (data not shown) (Liu et al, 1999).…”
Section: Identification Of Clone A-15mentioning
confidence: 85%
See 1 more Smart Citation
“…In vitro , the SINE analogs are induced by several stressful stimuli, including heat shock (Fornace & Mitchell, 1986; Liu et al ., 1995), DNA damage (Rudin & Thompson, 2001), viral infection (Singh et al ., 1985; Carey et al ., 1986; Panning & Smiley, 1995; Russanova et al ., 1995) and translational inhibition (Liu et al ., 1995). In vivo , the SINE B1 and B2 genes are induced after hyperthermic shock and ethanol administration in liver, spleen, kidney and testis (Li et al ., 1999). With the exception of the brain‐specific SINE BC1 expression (Tiedge et al ., 1991), there is only a single report describing the inducibility of the SINE B2 in the central nervous system (Liu et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , the SINE B1 and B2 genes are induced after hyperthermic shock and ethanol administration in liver, spleen, kidney and testis (Li et al ., 1999). With the exception of the brain‐specific SINE BC1 expression (Tiedge et al ., 1991), there is only a single report describing the inducibility of the SINE B2 in the central nervous system (Liu et al ., 1999). With regard to the B2 expression after global ischemia, our results are comparable with the previous study of Liu et al .…”
Section: Discussionmentioning
confidence: 99%